KINERJA SUPPLIER BAHAN PANGAN DI RUMAH SAKIT X DEPOK - Medah, Fenycia Utari Firstianti; Saidah, Zumi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Supplier performance is an indicator that can be used as a first step for the supplier’s success in the relationship with customers in the future. Supplier with bad performance might disturb the business activity, whereas the good one would impact positively to company success. The purpose of this research is to analyze food supplier performance of RS X Depok including the impacts for the hospital. This research is using descriptive methodology with qualitative approach. Data collection was performed by doing some structured interviews. The chosen supplier performance indicators to be used to analyze the food supplier performance were Replenishment Lead Time, On-Time Performance, Supply Flexibility, Delivery Frequency, Supply Quality, Inbound Transportation Cost, Pricing Terms, Information Coordination Capability and Supplier Viability. The result of this research showed both suppliers had a good performance. Supplier BJ was excellent in every aspect of supplier performance. Meanwhile, Supplier AM showed a good performance in almost every aspect but has supply quality shortcomings. Sometimes, the meat weight was inappropriate so it had to be exchanged and the dirty eggshell had to be cleaned several times. Based on their performance, the food suppliers also positively impact the hospital.